The Holy Spirit in the New Testament a Pentecostal guide - Simmons, William A. 1954- (Downers Grove, IL ivp Academic, 2021)
Introduction: Why "Pentecostal themes of the New Testament"? -- The Holy Spirit in Matthew : hallmark of the Kingdom -- The Holy Spirit in Mark : authority and obedience -- The Holy Spirit in Luke : good news for the poor and freedom for the captives -- The Holy Spirit in John : the Spirit of truth -- Holy Spirit in Acts : a promise kept -- The Holy Spirit in Romans : the Spirit of adoption -- The Holy Spirit in 1 Corinthians : the Spirit of wisdom and grace -- The Holy Spirit in 2 Corinthians : the Spirit of the new covenant -- The Holy Spirit in Galatians : the Spirit of freedom -- The Holy Spirit in Ephesians, Colossians and Philemon : the Spirit of wisdom and revelation -- The Holy Spirit in Philippians : the Spirit of joy -- The Holy Spirit in 1 & 2 Thessalonians : eschatology and ethics -- The Holy Spirit in the Pastoral Epistles : the Spirit of power, love and self-control -- The Holy Spirit in Hebrews : the testimony of the Spirit -- The Holy Spirit in James : the wisdom of God -- The Holy Spirit in 1 & 2 Peter : God's answer to suffering for Christ -- The Holy Spirit in the Johannine Epistles : the Spirit of truth -- The Holy Spirit in Jude : praying in the Spirit -- The Holy Spirit in Revelation : the spirit of prophecy.
"With an ever-increasing number of Christians worldwide self-identifying as Pentecostal or charismatic, the church needs a Spirit-centered interpretation of Scripture informed by a Pentecostal lens. In this accessible New Testament introduction, each chapter explores the presence of the Spirit in a biblical book, then offers devotional applications to help readers respond to the text"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Holy Spirit -- Biblical teaching; Pentecostalism